An experimental and numerical study of the pre-dissociated NH3 enrichment effect on TRF fuel laminar burning velocity - Leilei Liu; Xinlu Han; Ye Yuan; Jiayi Lin; Meiying Han; Hongqing Feng (Fuel, 2026)

OES-guided electrical and hydrodynamic control for efficient NOx synthesis in an advanced plasma-liquid bubble discharge reactor - Jianfei Guo; Leilei Dai; Michelle Zhou; Xiangyang Lin; Xukun Zhu; Yuxi Chen; Juer Liu; Yuting Li; Kirk Cobb; Nan Zhou; Roger Ruan (Chemical Engineering Journal, 2026)

Acoustic Flutter Processing in the Inferior Colliculus of Awake Marmosets: Complementary Rate Coding Modulated by Acoustic Parameters - Siyi Bai; Xinyuan Cao; Min Xie; Guanglong Sun; Xiaohui Wang; Leilei Zheng; Xinjian Li; Zheng Lin; Lixia Gao (Neuroscience Bulletin, 2026)
The acoustic flutter is processed through complementary monotonic rate coding and cannot be modulated by other acoustic parameters in the auditory cortex (AC). However, it remains unclear how the inferior colliculus (IC) encodes acoustic flutter, especially when changing other acoustic parameters. Here, we recorded IC neural activity in response to acoustic flutter and determined the existence of conjunctive processing between repetition rate and other acoustic parameters. We found that most IC neurons also encode the repetition rate at the flutter range through complementary monotonic rate coding. In addition, although the acoustic parameters did not change their monotonicity, most IC neurons encode both repetition rate and other acoustic parameters, different from the flutter processing in AC. Thus, complementary monotonic rate coding for acoustic flutter was widespread in the auditory system; however, coding specificity for repetition rate increased from IC to AC, and the capacity for conjunctive coding with other acoustic parameters decreased.

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

Multimodal detection of microplastics in human kidney stones and multi-omics exploration of renal cell metaflammation - Qingli Zeng; Jinhui Tang; Leilei Zhan; Ruiyin Liang; Chuanli Yang; Ruibin Cai; Jieyu Luo; Jia Xu; Tao Liu; Hongyan Wei; Lin Che (Journal of Hazardous Materials, 2026)

A multi-component recycling strategy for photovoltaic waste: Co-recovering silicon and PVDF into Ag–F reinforced Si/C anodes - Yihao Li; Yiqing Chen; Xiaojiao Zhang; Yaoguang Guo; Shuai Chen; Jie Yang; Tie Lin; Haodong Ran; Yang Zhang; Qin Xu; Yanlin Wu; Hao Yuan; et al. (Resources, Conservation and Recycling, 2026)

Comparative analysis of laminar burning velocity of CH4 + H2 flame across a broad temperature range under atmospheric pressure - Jiayi Lin; Zhongqian Ling; Leilei Liu; Ye Yuan; Jiamin Li; Dingkun Yuan; Jiangrong Xu; Xinlu Han; Zhihua Wang (Fuel, 2026)

An experimental and kinetic modeling study of the chemical/thermal/ dilution and blending effects on the laminar burning velocities of TRF flames - Leilei Liu; Ye Yuan; Jiayi Lin; Meiying Han; Xinlu Han; Hongqing Feng (Fuel, 2026)

Observation-constrained long-term simulations of water dynamics and groundwater recharge under intensive agriculture in the North China Plain - Lin Wu; Leilei Min; Meiying Liu; Wolfgang Kinzelbach; Shiqing Wang; Ahmed Mady; Yanjun Shen (Groundwater for Sustainable Development, 2025)

Outliers removal based on geometric coherence constraints in remote sensing image matching - Leilei Jia; Lin Shi; Dongdong Shi; Limin Liu (International Journal of Remote Sensing, 2025)

Identification of Dendrobium officinale species and authentication of commercial products by DNA barcoding and high-resolution melting analysis - Zhilong He; Zhao Yang; Cui Dong; Shanshan Yan; Jing Lin; Hexigeduleng Bao; Fan Tang; Leilei Zhang; Cheng Zhu; Yan Hu; Yanfei Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Chronic exposure to liquid crystal monomer EBCN at environmentally relevant concentrations induces testicular dysfunction via the gut-testis axis - Jun Wu; Daojun Lv; Wanmei Lin; Yiyou Mao; Yanqing Xia; Leilei Feng; Tianxin Zhao; Xiangming Mao; Fangpeng Shu; Haibin Guo (Journal of Hazardous Materials, 2025)

Effect of pre-grouting on the ground deformation and its mechanism in the construction of tunnels with small-spacing and large-section - Dechun Lu; Xu Meng; Qingtao Lin; Leilei Shi; Xiuli Du (Transportation Geotechnics, 2025)

Evaluating the impacts of converting grain to vegetable fields on nitrate transport in the deep vadose zone of the North China Plain - Meiying Liu; Leilei Min; Lin Wu; Yucui Zhang; Yongqing Qi; Shiqin Wang; Binbin Liu; Di Geng; Yanjun Shen (Journal of Geographical Sciences, 2025)

Predicting rice phenology across China by integrating crop phenology model and machine learning - Jinhan Zhang; Xiaomao Lin; Chongya Jiang; Xuntao Hu; Bing Liu; Leilei Liu; Liujun Xiao; Yan Zhu; Weixing Cao; Liang Tang (Science of The Total Environment, 2024)

Variation of nitrate sources affected by precipitation with different intensities in groundwater in the piedmont plain area of alluvial-pluvial fan - Heping Sun; Wenbo Zheng; Shiqin Wang; Lin Ma; Leilei Min; Yanjun Shen (Journal of Environmental Management, 2024)

Error modeling and hierarchical Bayesian fusion for spaceborne and ground radar rainfall data - Leilei Kou; Ying Mao; Zhengjian Lin; Haiyang Gao; Zhigang Chu; Aijun Chen (Journal of Hydrology, 2024)

Climate and mineral accretion as drivers of mineral‐associated and particulate organic matter accumulation in tidal wetland soils - Chuancheng Fu; Yuan Li; Lin Zeng; Chen Tu; Xiaoli Wang; Haiqing Ma; Leilei Xiao; Peter Christie; Yongming Luo (Global Change Biology, 2024)
Tidal wetlands sequester vast amounts of organic carbon (OC) and enhance soil accretion. The conservation and restoration of these ecosystems is becoming increasingly geared toward “blue” carbon sequestration while obtaining additional benefits, such as buffering sea‐level rise and enhancing biodiversity. However, the assessments of blue carbon sequestration focus primarily on bulk SOC inventories and often neglect OC fractions and their drivers; this limits our understanding of the mechanisms controlling OC storage and opportunities to enhance blue carbon sinks. Here, we determined mineral‐associated and particulate organic matter (MAOM and POM, respectively) in 99 surface soils and 40 soil cores collected from Chinese mangrove and saltmarsh habitats across a broad range of climates and accretion rates and showed how previously unrecognized mechanisms of climate and mineral accretion regulated MAOM and POM accumulation in tidal wetlands. MAOM concentrations (8.0 ± 5.7 g C kg −1 ) (±standard deviation) were significantly higher than POM concentrations (4.2 ± 5.7 g C kg −1 ) across the different soil depths and habitats. MAOM contributed over 51.6 ± 24.9% and 78.9 ± 19.0% to OC in mangrove and saltmarsh soils, respectively; both exhibited lower autochthonous contributions but higher contributions from terrestrial or marine sources than POM, which was derived primarily from autochthonous sources. Increased input of plant‐derived organic matter along the increased temperature and precipitation gradients significantly enriched the POM concentrations. In contrast, the MAOM concentrations depended on climate, which controlled the mineral reactivity and mineral–OC interactions, and on regional sedimentary processes that could redistribute the reactive minerals. Mineral accretion diluted the POM concentrations and potentially enhanced the MAOM concentrations depending on mineral composition and whether the mineral accretion benefited plant productivity. Therefore, management strategies should comprehensively consider regional climate while regulating sediment supply and mineral abundance with engineering solutions to tap the OC sink potential of tidal wetlands.

Synergistic effect between monophosphine species for regioselective hydroformylation of olefin with CO2 - Guoqing Wang; Miao Jiang; Zhao Sun; Leilei Qian; Guangjun Ji; Lei Ma; Cunyao Li; Zhaozhan Wang; Yong Yang; Xiangsong Lin; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2023)

Catalytic fast co-pyrolysis of Douglas Fir and low-density polyethylene with nanocellulose-derived carbon catalyst for enhancing selectivity of hydrogen in syngas and mono-aromatic hydrocarbon in bio-oil products - Rongge Zou; Chenxi Wang; Moriko Qian; Ryan Lei; Yunfeng Zhao; Qingfa Zhang; Erguang Huo; Xiao Kong; Xiaona Lin; Lu Wang; Xuesong Zhang; Austin Gluth; et al. (Chemical Engineering Journal, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Phenol degradation at high salinity by a resuscitated strain Pseudomonas sp. SAS26: kinetics and pathway - Shusheng Zhang; Zijing An; Xiaomei Su; Aiqin Hou; Leilei Liu; Lihua Zhang; Qiuyang He; Faqian Sun; Zupei Lei; Hongjun Lin; Jiahou Lai (Journal of Environmental Chemical Engineering, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Comparisons of three-dimensional reflectivity and precipitation rate from GPM dual-frequency precipitation radar and ground dual-polarization radar - Leilei Kou; Ying Mao; Zhixuan Wang; Zhengjian Lin; Yao Chen; Haiyang Gao; Zhigang Chu; Aijun Chen (Atmospheric Research, 2023)

Whole-genome sequencing and comparative analysis of Helicobacter pylori GZ7 strain isolated from China - Xiaoyan Zeng; Lin Xiong; Wenling Wang; Yan Zhao; Yuan Xie; Qinrong Wang; Qifang Zhang; Leilei Li; Cencen Jia; Yonghui Liao; Jianjiang Zhou (Folia Microbiologica, 2022)

Calcium Homeostasis in Parkinson’s Disease: From Pathology to Treatment - Jingxian Zhang; Qingqing Shen; Yue Ma; Lin Liu; Wenting Jia; Leilei Chen; Junxia Xie (Neuroscience Bulletin, 2022)

Application of hydrogen-rich water modulates physio-biochemical functions and early growth of fragrant rice under Cd and Pb stress - Lin Ma; Leilei Kong; Runfei Gui; Xiaojuan Yang; Jianwen Zhang; Qi Gong; Dejun Qin; Maosen Zhuang; Umair Ashraf; Zhaowen Mo (Environmental Science and Pollution Research, 2021)

Control System Design and Implementation at Flexible, Distributed Offshore Sensor Test Sites in the Yangtze Estuary Area - Qingsong Hu; Chao Jiang; Lin Du; Jun Li; Leilei Chen; Peng Xiang; Hongcheng Zhang; Hafiz Abd ur Rahman (Journal of Ocean University of China, 2021)

Deep Placement of Nitrogen Fertilizer Affects Grain Yield, Nitrogen Recovery Efficiency, and Root Characteristics in Direct-Seeded Rice in South China - Yunyan Chen; Pingshan Fan; Zhaowen Mo; Leilei Kong; Hua Tian; Meiyang Duan; Lin Li; Liji Wu; Zaimang Wang; Xiangru Tang; Shenggang Pan (Journal of Plant Growth Regulation, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

Differential antigen expression between human eccrine sweat glands and hair follicles/pilosebaceous units - Leilei Cao; Liyun Chen; Haihong Li; Zairong Wei; Sitian Xie; Mingjun Zhang; Yao Lin; Haihua Huang (Journal of Molecular Histology, 2019)

Constant hypoxia inhibits osteoclast differentiation and bone resorption by regulating phosphorylation of JNK and IκBα - Zhenzhen Ma; Ruohan Yu; Jinxia Zhao; Lin Sun; Leilei Jian; Changhong Li; Xiangyuan Liu (Inflammation Research, 2019)

The Cooling Trend of Canopy Temperature During the Maturation, Succession, and Recovery of Ecosystems - Hua Lin; Zexin Fan; Leilei Shi; Altaf Arain; Harry McCaughey; Dave Billesbach; Mario Siqueira; Rosvel Bracho; Walter Oechel (Ecosystems, 2017)

Molecular characterization of swine leukocyte antigen class I genes by sequence-based and PCR-SSP method in Guizhou minipigs - Jihan Xia; Zizhan Liu; Leilei Xin; Zaigui Wang; Lin Qian; Shuguang Wu; Shulin Yang; Kui Li (Molecular Biology Reports, 2014)